2021
DOI: 10.1111/cns.13656
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal raphe serotonergic neurons promote arousal from isoflurane anesthesia

Abstract: Aims General anesthesia has been widely applied in surgical or nonsurgical medical procedures, but the mechanism behind remains elusive. Because of shared neural circuits of sleep and anesthesia, whether serotonergic system, which is highly implicated in modulation of sleep and wakefulness, regulates general anesthesia as well is worth investigating. Methods Immunostaining and fiber photometry were used to assess the neuronal activities. Electroencephalography spectra and burst‐suppression ratio (BSR) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Combined with this study, the conclusions of our research supports the important role of 5-HT 1A receptor in the recovery from general anesthesia. For the 5-HT 2A/C receptor, some studies have shown that the activation of serotonergic neurons may partially promote the awakening of general anesthesia through the 5-HT 2C receptor [41] . Through intracerebroventricular injection of 5-HT 2A/C receptor agonist DOI and 5-HT 2C receptor antagonist RS-102221, it was found that activating 5-HT 2A/C receptor can shorten the awakening time and inhibiting 5-HT 2C receptor can prolong the awakening time.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with this study, the conclusions of our research supports the important role of 5-HT 1A receptor in the recovery from general anesthesia. For the 5-HT 2A/C receptor, some studies have shown that the activation of serotonergic neurons may partially promote the awakening of general anesthesia through the 5-HT 2C receptor [41] . Through intracerebroventricular injection of 5-HT 2A/C receptor agonist DOI and 5-HT 2C receptor antagonist RS-102221, it was found that activating 5-HT 2A/C receptor can shorten the awakening time and inhibiting 5-HT 2C receptor can prolong the awakening time.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have typically focused on one of the three main varieties of arousal: wakeful, autonomic, or affective (Satpute et al, 2019). Investigations of the neural basis of sleep and wakefulness mostly used EEG desynchronization and decreases in EEG power as measures of wakeful arousal, and attributed a wake-promoting function to the activity of cholinergic cells in the basal forebrain (Han et al, 2014; Irmak and de Lecea, 2014; Xu et al, 2015) (but see Anaclet et al, 2015; Zant et al, 2016), noradrenergic (Berridge et al, 2012), serotonergic (Li et al, 2021; Monti, 2011), and dopaminergic (Cho et al, 2017; Eban-Rothschild et al, 2016) neurons located in the pons and the midbrain, as well as histaminergic (Fujita et al, 2017; Thakkar, 2011) and orexinergic (Sasaki et al, 2011; Tsunematsu et al, 2013; Tyree et al, 2018) hypothalamic neurons. The wake-promoting effects of the activity of these cell groups are antagonized by accumulation of extracellular adenosine (homeostatic sleep drive) and modulated by the oscillations in the activity of neurons in the suprachiasmatic hypothalamic nucleus (circadian regulation) (Brown et al, 2012; Saper et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using optogenetic and chemogenetic approaches, activation of DRN 5-HT neurons reduced the depth of anesthesia with respect to a decrease in the burst-suppression ratio during anesthesia maintenance and facilitated the emergence from isoflurane anesthesia. The emergence-promoting function of DRN 5-HT neurons could be achieved by 5-HT 1A or 2C receptors in the brain [ 111 ].…”
Section: Other Circuits Involved In the Arousal Of Anesthesiamentioning
confidence: 99%